(untitled) (Experimental biology, 2022)
The article describes the features of the structure of cenopopulations and the distribution of the rare, endemic plant Allochrusa gypsophiloides. 3 populations, 4 cenopopulations were studied. At the same time, a map-scheme on plant species distribution was drawn up between 2011 and 2022. A DEM map was created for the distribution zones of the 3 populations found in the study. The average species density varied from 1.5 to 2.9 pcs. Cenopopulation - the dominance of generative individuals 1, 2 and 3,4 corresponds to the state of CP-1 - absolute maximum g1(20,0%), cenopopulation 2-3 and 4- varies from 18,52%, 24,14% and 33,34%. The number of postgenerative individuals in the cenopopulations is not significantly high, varying within the subsenile ss (0% -13.34%). Illustrative graphs, tables on age spectrum of Allochrusa gypsophiloides species cenopopopulations were created and the current state of structural features of distribution and cenopopulations of the plant was evaluated.